Antenatal intervention for congenital fetal lower urinary tract obstruction (LUTO): a systematic review and meta-analysis. (2nd August 2020) - Saccone, Gabriele; D'Alessandro, Pietro; Escolino, Maria; Esposito, Rosanna; Arduino, Bruno; Vitagliano, Amerigo; Quist-Nelson, Johanna; Berghella, Vincenzo; Esposito, Ciro; Zullo, Fulvio
Abstract: Objective: To evaluate the effectiveness of antenatal intervention for the treatment of congenital lower urinary tract obstruction (LUTO) in improving perinatal survival and postnatal renal function. Methods: Electronic databases were searched from their inception until May 2018. Selection criteria included randomized controlled trials and nonrandomized studies including fetuses with ultrasound evidence of LUTO evaluating antenatal intervention for improving perinatal outcomes. Any type of antenatal bladder drainage technique was analyzed. The primary outcome was perinatal survival. The secondary outcome was postnatal survival with normal renal function. The summary measures were reported as summary odds ratio (OR) with 95% of confidence interval (CI). Results: Ten articles with a total of 355 fetuses were included in the meta-analysis. Inclusion criteria of the selected studies were singleton pregnancy with severe LUTO confirmed on detailed fetal ultrasound examination. Nine studies analyzed the efficacy of vesico-amniotic shunt performed in the second trimester. The overall estimate survival was higher in the vesico-amniotic shunt group compared to the conservative group (OR: 2.54, 95% CI: 1.14–5.67). 64/112 fetuses (57.1%) survived in the vesico-amniotic shunt group compared to 52/134 (38.8%) in the control group. Five studies reported on postnatal renal function between 6 months and 2 years. Rate of good postnatal renal function was higher in the vesico-amniotic shunt group compared to the conservative group (OR: 2.09, 95% CI: 0.74–5.9). Fetal cystoscopy was performed in only two included studies. Overall, 45 fetuses underwent fetal cystoscopy. The perinatal survival was higher in the cystoscopy group compared to the conservative management group (OR: 2.63, 95% CI: 1.07–6.47). Normal renal function was noted in 13/34 fetuses in the cystoscopy group versus 12/61 in the conservative management group at 6 months follow-up (OR: 1.75, 95% CI: 1.05–2.92) Conclusions: Antenatal bladder drainage appears to improve perinatal survival in cases of LUTO.